2020
DOI: 10.2355/isijinternational.isijint-2019-401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prior Structure to Intercritical Annealing on Rapid Formation of Ultrafine Ferrite + Austenite Structure and Mechanical Properties in 0.1%C-2%Si-5%Mn Steels

Abstract: Ultrafine ferrite + austenite steels with the chemical composition of 0.1%C-2%Si-5wt%Mn show excellent strength (TS = 1 200 MPa) and high ductility (TEl = 25%) balance, compared to conventional TRIP steels. This steel is expected as the third generation advanced high-tensile strength steels (AHSS). This steel can be produced by a simple intercritical annealing, however, longer annealing time is necessary to obtain appropriate ferrite + austenite structure. It is difficult to produce this steel by continuous an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
1
0
2
Order By: Relevance
“…This cementite was distributed both at the grain boundaries and within the grains. Our prior work has also demonstrated that the cementite phase was enriched with Mn, resulting in the formation of the compound (Fe,Mn) 3 C. 45) 3. 1.…”
Section: C Addition and Microstructural Changementioning
confidence: 91%
“…This cementite was distributed both at the grain boundaries and within the grains. Our prior work has also demonstrated that the cementite phase was enriched with Mn, resulting in the formation of the compound (Fe,Mn) 3 C. 45) 3. 1.…”
Section: C Addition and Microstructural Changementioning
confidence: 91%
“…自動車用の次世代高張力鋼として中 Mn 鋼が着目され る。中 Mn 鋼は 3-10% 程度の Mn を含む低炭素鋼であり, フェライト母相と残留オーステナイトよりなる組織形態を 示す。残留オーステナイトの変態誘起塑性(Transformation induced plasticity: TRIP)効果により優れた延性を有する鋼 材となる 1,2) 。その中でも冷延後に焼鈍したものは 10%程 度,あるいはそれ以上の大きな Lüders 変形(Lüders 帯を伴 う不均一変形)が生じる。Lüders 変形分だけ加工硬化曲線 はオフセットされたような形となり,高強度であるにもか かわらず極めて高い一様伸びを示す [3][4][5] 。一方で Lüders 変 形はストレッチャーストレインのようなプレス成形時の不 良となることが知られており 6) , その対策を考える上で精 度の良い力学モデルが必要となる。 ここで,Lüders 変形とこれに伴う降伏伸びは古くから 知られる鋼材の降伏現象の基本的な特徴の一つである。 Lüders 変形においては負荷された応力が上降伏点に達した 際に降伏を開始し,即座に公称応力は下降伏点まで低下, ある伸び量(降伏伸び)に達するまで加工硬化せずに一定 の応力を保ったまま塑性変形が進む。そのメカニズムは未 だ不明なところが多いが,炭素原子と転位との固着がはず れる 7) , あるいは可動転位の急激な増殖 8,9) による降伏応力 低下が引き起こす現象として理解されている。 Lüders 帯は降伏応力の低下に起因する不均一変形によっ て生じたせん断帯であり,降伏伸び中において引張試験片 の掴み部付近から生じたものが長手方向に複数回伝播する ことを繰り返す。このため,Lüders 帯の伝播挙動やその内 部の金属組織状態と塑性変形中の応力低下・停留は相関 する [10][11][12][13] 。実際,Lüders 帯の伝播とともに伸び量は増すの で,せん断帯の挙動が引張試験結果(応力と伸びの関係) に大きく影響を与えることに間違いはない。その証とし て,測定される降伏伸び量はゲージ長さやひずみ速度に強 く依存し,ゲージ長さが短くなるほど,そしてひずみ速度 が小さくなるほど降伏伸びは減少することが報告されてい る 14,15) 。 力学的には一様変形中の隠された高次変形モードが Lüders 帯(せん断帯)として発現したものと捉えること ができる 16) 。このような高次モードの発現は分岐現象と して知られる。分岐現象としてのせん断帯発生は加工硬 化率が特定の値以下になった際に必ず発生してしまうた め,Lüders 変形のような加工硬化率が 0 以下となる状況に おいてせん断帯発生は必然である。これらの知見をもとに 流動応力の低下項を導入した構成則が既に提案されてお り 17,18) , 有限要素解析(FEM)に組み込むことで Lüders 帯 の発生と伝播,その結果としての降伏伸びが再現されてい る 19)…”
Section: 緒言unclassified
“…松野 崇 1,2) * ・古川 洸希 1) ・興津 貴隆 3) ・小山 元道 4) ・土山 聡宏 5) Local Yield Stress and its Unusual Independence on Multi-axial Stress States during Lüders Deformation of Medium-Mn, High-strength Steel…”
Section: 中Mn 鋼の降伏伸び変形における局所変形抵抗と 応力多軸状態に対するその特異な独立性unclassified